Descriptive analysis of the deaf-to-non-deaf discourse in Short Message System (SMS) - Lawagan, Bency Joy B. (2014., 2014)
This study is a descriptive analysis of Deaf to non-deaf discourse in Short Message System (SMS). It is a qualitative study that focuses on five conversations. Using the Multimodal Analysis, it explores the role of the SMS as a medium in effective communication.
The structures and patterns of the Deaf and non-deaf in conversation observed are more or less the same. The minimal limitations seen in communication can be ascribed to the first language interference of the Deaf, sign language being their first language.
The study explores the equality in language acquisition and communication competence between the Deaf and non-deaf -- Author's abstract.
Thesis (Bachelor of Arts in Language and Literature)--University of the Philippines Baguio, 2014.
Includes bibliographical references (leaves 72-74).
Keywords: Text messages (Telephone systems).; Deaf -- Means of communication; Nonverbal communication